Physiological and psychological stress responses to labor and delivery during COVID-19 pandemic: a cohort study. (2nd October 2022) - Asali, Aula; Farladansky-Gershnabel, Sivan; Hasky, Noa; Elbaz, Michal; Fishman, Ami; Ravid, Dorit; Wiser, Amir; Biron-Shental, Tal; Berkovitz, Arie; Miller, Netanella
Abstract: Objective: To evaluate objective (saliva cortisol) and subjective (questionnaire) stress levels during the Coronavirus disease (COVID-19) pandemic compared to before the pandemic and their effects on obstetric and neonatal outcomes. Methods: This cohort study included 36 women with low-risk, singleton, term deliveries at a tertiary academic center during the COVID-19 pandemic and 49 who delivered before. Physiological stress was evaluated with salivary cortisol measurements, and emotional stress with stress scale questionnaires (0–10) during active and full dilation stages of labor, and 2-min postpartum. Cord blood cortisol and pH were obtained. Delivery mode, complications, and neonatal outcomes were evaluated. Results: Psychological stress was higher for the COVID-19 group compared to controls during full dilation (6.2 ± 3.4 vs. 4.2 ± 3, p = .009). The COVID-19 group had significantly lower cord cortisol levels (7.3 vs. 13.6 mcg/dl, p = .001). No differences were found regarding salivary cortisol level assessments at active, full dilation and 2-min post-delivery ( p = .584, p = .254, p = .829, respectively). No differences were found regarding pH < 7.1 ( p = .487), 1- and 5-min Apgar scores < 7 ( p = .179) and neonatal weight ( p = .958). Conclusions: Women who delivered during COVID-19 pandemic had higher stress levels at full dilation and lower cord cortisol levels, as may be expected after exposure to a chronic stressor.